Agricultural Market Information Virtual Library - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
The Agricultural Market Information Virtual Library, maintained by the Department of Agricultural Economics, Michigan State University, contains links to a vast range of sources of agricultural market information, e-commerce sites, etc.